Ontogenetic Patterning of Human Subchondral Bone Microarchitecture in the Proximal Tibia - Jesse R. Goliath; James H. Gosman; Sam D. Stout; Timothy M. Ryan (Biology, 2022)
High-resolution computed tomography images were acquired for 31 proximal human tibiae, age 8 to 37.5 years, from Norris Farms #36 cemetery site (A.D. 1300). Morphometric analysis of subchondral cortical and trabecular bone architecture was performed between and within the tibial condyles. Kruskal–Wallis and Wilcoxon signed-rank tests were used to examine the association between region, age, body mass, and each morphometric parameter. The findings indicate that age-related changes in mechanical loading have varied effects on subchondral bone morphology. With age, trabecular microstructure increased in bone volume fraction (p = 0.033) and degree of anisotropy (p = 0.012), and decreased in connectivity density (p = 0.001). In the subchondral cortical plate, there was an increase in thickness (p < 0.001). When comparing condylar regions, only degree of anisotropy differed (p = 0.004) between the medial and lateral condyles. Trabeculae in the medial condyle were more anisotropic than in the lateral region. This research represents an innovative approach to quantifying both cortical and trabecular subchondral bone microarchitecture in archaeological remains.